Insurance and behavioral economics improving decisions in the most misunderstood industry - Kunreuther, Howard; Pauly, Mark V., 1941-; McMorrow, Stacey; ProQuest (firma) (Cambridge : Cambridge University Press, 2013)
"This book examines the behavior of individuals at risk, insurance industry decision makers and policy makers involved in the selling, buying, and regulating of insurance"--
Machine generated contents note: 1. Purposes of this book; 2. An introduction to insurance in practice and theory; 3. Anomalies and rumors of anomalies; 4. Behavior consistent with benchmark models; 5. Real world complications; 6. Why people do or do not demand insurance; 7. Demand anomalies; 8. Descriptive models of insurance supply; 9. Anomalies on the supply side; 10. Design principles for insurance; 11. Strategies for dealing with insurance-related anomalies; 12. Innovations in insurance markets through multi-year contracts; 13. Publicly-provided social insurance.
Includes bibliographical references and indexes.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Risk (Insurance); Insurance -- Decision making; Consumer behavior; elektronické knihy; electronic books